2010
DOI: 10.4049/jimmunol.1001628
|View full text |Cite
|
Sign up to set email alerts
|

IDO Upregulates Regulatory T Cells via Tryptophan Catabolite and Suppresses Encephalitogenic T Cell Responses in Experimental Autoimmune Encephalomyelitis

Abstract: Experimental autoimmune encephalomyelitis (EAE) is a Th1 and Th17 cell-mediated autoimmune disease of the CNS. IDO and tryptophan metabolites have inhibitory effects on Th1 cells in EAE. For Th17 cells, IDO-mediated tryptophan deprivation and small molecule halofuginone-induced amino acid starvation response were shown to activate general control nonrepressed 2 (GCN2) kinase that directly or indirectly inhibits Th17 cell differentiation. However, it remains unclear whether IDO and tryptophan metabolites impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
282
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 317 publications
(294 citation statements)
references
References 42 publications
10
282
0
2
Order By: Relevance
“…Indeed, indoleamine 2, 3-dioxygenase (IDO), which is expressed in some DC and macrophages and play an important role in promoting the formation of T regulatory cells. IDO induces tryptophan depletion and cell stress, which activates the general control nonrepressed 2 (GCN2) protein kinase-dependent pathway and has direct regulatory effect on cell survival and function of immune responses (41)(42)(43). Preliminary studies suggest that human monocyte derived DC treated with the stress inducing agents used in this study inhibit Treg formation.…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, indoleamine 2, 3-dioxygenase (IDO), which is expressed in some DC and macrophages and play an important role in promoting the formation of T regulatory cells. IDO induces tryptophan depletion and cell stress, which activates the general control nonrepressed 2 (GCN2) protein kinase-dependent pathway and has direct regulatory effect on cell survival and function of immune responses (41)(42)(43). Preliminary studies suggest that human monocyte derived DC treated with the stress inducing agents used in this study inhibit Treg formation.…”
Section: Discussionmentioning
confidence: 91%
“…MSCs from different sources were shown to induce tolerogenic DCs [12][13][14][15]21], but this is the first time showing what mechanisms operate between MSC-induced tolerogenic DCs and Treg cells. Namely, we found that IDO-1, ILT-3, and ILT-4 expressed by PL-MSC-developed DCs are crucial for the induction of functional Foxp3 + Treg cells, which is already described mechanism utilized by tolerogenic DCs [22,23]. Besides Foxp3, CD39 was recognized recently as a key marker of functional Treg cells [27].…”
Section: Discussionmentioning
confidence: 98%
“…To evaluate why PL-MSC-developed DCs possess lower allostimulatory ability and Th2 polarization, in spite of their phenotypical maturation, we studied the expression of coinhibitory molecules (IDO-1, ILT-3, and ILT-4) characteristic for tolerogenic DCs [22,23]. The pro-inflammatory cocktail reduced the expression of IDO-1 and ILT-3, and increased the expression of ILT-4 by control mDCs (Fig.…”
Section: Pl-msc-developed Dcs Induce Anergy and Functional Treg-cellmentioning
confidence: 99%
“…Underlined metabolites were measured by the LC-MS/MS method described amide (NAm) and nicotinic acid (NA) [6]. Most catabolites are biologically active and involved in the pathogenesis of many disease processes [7][8][9][10][11][12]. Furthermore, the interrelationship between metabolic pathways is of profound pharmacological and physiological importance as changes in one pathway might have secondary effects on the others [1].…”
Section: Introductionmentioning
confidence: 99%